Soil charge characteristics and sesquioxide properties in different land uses in Universiti Putra Malaysia Bintulu Campus, Sarawak - Jamaluddin, Siti Zubaidah (2018)
A research was conducted to determine the sesquioxide properties and charge characteristics in secondary forest and agriculture land (oil palm and rubber plantation) of Universiti Putra Malaysia (UPM), Bintulu Campus Sarawak. Six subplots were established in a 20 m x 20 m plot and soil sampling of different depth were carried out for topsoil (0 cm – 15 cm) and subsoil (15 cm – 30 cm). The charge characteristics of the three different soils were determined by the Point of Zero Charge Effect (PZSE). The soil samples were prepared for seven sets of different HCl concentration. The pH value before and after NaCl were added was recorded. The sesquioxide properties in the soil were extracted using method dithionate and oxalate extractable Al and Fe. The concentration of Al and Fe were determined by using atomic absorption spectroscopy (AAS). For charge characteristics, the result shows that there were significant difference value among the sites with the highest mean of 3.193 ± 0.234 in secondary forest. This was because, the soil in secondary forest development activity was higher compared to oil palm and rubber plantation due to the richness of organic matter in the topsoil. The sesquioxides properties results showed that there were no significant difference between the three different land uses that indicated that these lands received same amount of organic matter . Small difference in Al and Fe value indicates that the soil experienced desilication due to weathering and leaching in all land used. Overall, secondary forest has lower rate of weathering compared to oil palm and rubber plantation due to the higher PZSE value in that site. But in sesquioxide properties, there were not much difference in the three sites which means that desilication in soil because of weathering and leaching process were similar for the three sites.